A Study on the Educational Needs of the Managers of Shiraz Hospitals in relation to Management Skills - Ali Reza Yusefi; Ahmad Sadeghi (Kerman University of Medical Sciences, 2017)
Background & Objective: Identifying needs of hospital administrators is an important step in planning, implementation and evaluation of educational courses and is one of the important steps to empower hospital heads and consequently to improve the organizational performance. This study aimed to determine the educational needs of hospitals' heads in Shiraz/ Iran. Methods: This cross-sectional, descriptive-analytic study was done on 96 chief and midlevel managers of hospitals in Shiraz in 2015. The data gathering tool was POSDCORB questionnaire consisting of 54 questions in 7 areas of Planning, Organizing, Staffing, Directing, Coordinating, Reporting and Budgeting. Data were analyzed through SPSS23 software using ANOVA tests and t-Test. Results: Based on the obtained mean scores for each domain, educational needs were prioritized as budgeting (3.43 of 5), planning (3.40), coordinating (3.37), directing (3.25), organizing (3.21), recruitment (3.19) and reporting (3.08). Coordination skill showed significant relationship with level of education (P=0.041) and management experience (P=0.023).Planning skill had significant relationship with management experience (P= 0.021), level of education (P=0.036), work experience (P=0.012), and Field of Study (P= 0.026). There was also significant relationship between leadership skill and management experience (P=0.016). Conclusion: Skills such as budgeting and planning seem to be more required for hospital managers; therefore, it is necessary to pay special attention to holding training courses in these fields. Keywords: Educational Needs, Hospital Managers, Managerial Skills Citation: Yusefi Ali R, Sadeghi A. A Study on the Educational Needs of the Managers of Shiraz Hospitals in relation to Management Skills. Journal of Health Based Research 2017; 3(2): 175-186.